Sexual jokes and conversations at the workplace and their relation to employee well-being: Results from a longitudinal study - Sabine Hommelhoff; David Richter; Susanne Scheibe (Journal of Occupational and Organizational Psychology, 2024)
Ambient social sexual behaviour at work refers to sexual jokes and conversations at the workplace. Prior cross-sectional studies indicate that this behaviour is relatively widespread and tends to be associated with negative well-being. We revisit this research by investigating the outcomes of sexual jokes and conversations at work after 1 year in a comparatively large employee sample. The perceived frequency of sexual jokes and conversations at work was negatively related to job satisfaction and positively related to sick days and anger 1 year later, controlling for baseline levels. Moderating effects of gender and age were not significant. Half of the sample reported that such jokes and conversations were relatively common in their workplace, both before and after the onset of the MeToo movement. We discuss implications and propose ideas for studying the theoretical mechanisms of this phenomenon.
Keywords: 650; ambient social sexual behaviour; job satisfaction; negative affect; sick days; social sexual behaviour; well-being